Cancer Groundshot: Building a Robust Cancer Control Platform in Addition To Launching the Cancer Moonshot - Mutebi, Miriam; Dehar, Navdeep; Nogueira, Leticia M.; Shi, Kewei; Yabroff, K. Robin; Gyawali, Bishal (American Society of Clinical Oncology Educational Book, 2022)
Cancer Groundshot is a philosophy that calls for prioritization of strategies in global cancer control. The underlying principle of Cancer Groundshot is that onemust ensure access to interventions that are already proven towork before focusing on the development of newinterventions. In this article,we discuss the philosophy of Cancer Groundshot as it pertains to priorities in cancer care and research in low- andmiddle-income countries and the utility of technology in addressing global cancer disparities; we also address disparities seen in high-income countries. The oncology community needs to realign our priorities and focus on improving access to high-value cancer control strategies, rather than allocating resources primarily to the development of technologies that provide only marginal gains at a high cost. There are several low-hanging fruit actions that will improve access to quality cancer care in low- and middle-income countries and in high-income countries.Worldwide, cancermorbidity andmortality can be averted by implementing highly effective, low-cost interventions that are already known to work, rather than investing in the development of resource-intensive interventions towhichmost patientswill not have access (i.e.,we can use Cancer Groundshot to first savemore lives beforewe focus on themoonshots).
Keywords: Cancer; Control Platform; Cancer Moonshot